Assessment of Emission Characteristics and Performance Based on EGR and VCR with Jatropha Oil Methyl Ester and N-Butanol Blend - Pratik V. Swami*, Belagur K. Venkanna (International Journal of Advanced Science and Technology, 2020)
The intense change in the natural condition, quickly expanding the outflow of ozone-depleting substances and persistently expanding the cost of oil energizes there is a need for discovering cleaner and sustainable elective fuel. The key purpose of current research is towards the assessment of emission characteristics and performance of an engine with diesel without any modification by using jatropha oil methyl ester mixed along with N-Butanol at various exhaust gas recirculation (EGR) rate and variable compression ratio (VCR) on 4 strokes, with water cooling and distinct cylinder and perpetual speed. The common rail direct injection (CRDI) diesel engine was taken to perform experimental work. The information was broken down for different enforcement parameters, for example, emission parameters like hydrocarbons (HC), nitrogen oxide (NOx) smoke opacity (SO), carbon monoxide (CO) and performance influences such as brake thermal efficiency (BTE) and brake specific fuel consumption (BSFC). The collective influence of butanol blending, EGR and VCR shows the lower NOx emission.